2016
DOI: 10.1007/s00345-016-1815-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence in female urethral diverticulectomy: a retrospective study of 66 patients

Abstract: The surgical outcomes of urethral diverticulectomies were acceptable. Multiple diverticula, proximal diverticula and previous urethral surgery were three independent risk factors for recurrent diverticula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…In the same way, it has been reported that the more difficult the diverticulectomy, in particular due to multiple diverticula, proximal diverticula, and previous urethral surgery, the higher the rate of diverticulum recurrence. 11 Pre-operative assessment of patients with T2 weighted pelvic MRI scanning appears to be the most accurate method of diagnosing UD with high sensitivity, specificity, PPV and NPV of 100%, 83%, 92%, and 100%, respectively, 12 and provides detailed information regarding configuration and location.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, it has been reported that the more difficult the diverticulectomy, in particular due to multiple diverticula, proximal diverticula, and previous urethral surgery, the higher the rate of diverticulum recurrence. 11 Pre-operative assessment of patients with T2 weighted pelvic MRI scanning appears to be the most accurate method of diagnosing UD with high sensitivity, specificity, PPV and NPV of 100%, 83%, 92%, and 100%, respectively, 12 and provides detailed information regarding configuration and location.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, only eight subjects required reoperation. According to our previous study, women with multiple and proximal diverticula could be at an increased risk of recurrence (9). In our study, these two factors were examined after surgery.…”
Section: Discussionmentioning
confidence: 94%
“…The participant's clinical characteristics were collected and recorded. Fellowship-trained urologists at our institution performed all urethral diverticulectomies in a standard manner, as previously described (9). The steps of this procedure include careful dissection, complete excision and watertight three-layer closure without tension (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several known postoperative complications reported in the literature including urethral stricture, ureterovaginal fistula, stress incontinence, and recurrent UTIs [ 14 ]. The risk of complications increases with repeat procedures [ 15 ].…”
Section: Introductionmentioning
confidence: 99%